2003
DOI: 10.1152/ajpcell.00145.2002
|View full text |Cite
|
Sign up to set email alerts
|

PDGF upregulates delayed rectifier via Src family kinases and sphingosine kinase in oligodendroglial progenitors

Abstract: An increase in the expression of the delayed rectifier current ( I K) has been shown to correlate with mitogenesis in many cell types. However, pathways involved in the upregulation of I K by growth factors in oligodendroglial progenitors (OPs) have not been well-elucidated. In this study, we found that treatment with platelet-derived growth factor (PDGF) and basic fibroblast growth factor but not ciliary neurotrophic factor resulted in increased I K density and upregulation of Kv1.5 and Kv1.6 mRNA transcripts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 52 publications
5
19
0
Order By: Relevance
“…A proportion of white matter NG2 ϩ cells in situ were proliferative, whereas virtually all O4 ϩ cells were postmitotic. These data agree with previous in vitro studies demonstrating a correlation between expression of this channel and proliferative capacity (Gallo et al, 1996;Knutson et al, 1997;Chittajallu et al, 2002;Soliven et al, 2003). However, the fact that white matter O4 ϩ cells identified in this study are nonproliferative but display a significant and measurable I KDR raises an important issue.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A proportion of white matter NG2 ϩ cells in situ were proliferative, whereas virtually all O4 ϩ cells were postmitotic. These data agree with previous in vitro studies demonstrating a correlation between expression of this channel and proliferative capacity (Gallo et al, 1996;Knutson et al, 1997;Chittajallu et al, 2002;Soliven et al, 2003). However, the fact that white matter O4 ϩ cells identified in this study are nonproliferative but display a significant and measurable I KDR raises an important issue.…”
Section: Discussionsupporting
confidence: 92%
“…We have shown previously that (1) Kv1.3 and Kv1.5 but not Kv1.4 or Kv1.6 subunit proteins are upregulated by PDGF in OPs in vitro, and (2) selective pharmacological inhibition of Kv1.3 alone elicits cell cycle arrest in proliferating OPs in vitro . It has also been demonstrated that levels of Kv1.5 mRNA are upregulated in cultured OPs after PDGF treatment (Soliven et al, 2003). It is therefore possible that only certain Kv1 subunits (e.g., Kv1.3 and/or Kv1.5) are downregulated during NG2…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of CG4 cells with the SFK inhibitors SU6656 (2 m and 10 M) or PP2 (2 m and 10 M) resulted in a decrease in the number of cells, suggesting that SFKs are required for CG4 growth (data not shown). This result is similar to previous findings that SFKs are required for PDGFinduced OPC proliferation (45,46).…”
Section: Fyn Is Required For Ras and Rho Inactivation And Accumulatiosupporting
confidence: 93%
“…formation and chemotaxis, activation of NADPH oxidase, and increased expression of delayed rectifier current (15,(39)(40)(41). However, whereas cell movement toward PDGF depends on S1P receptor activation, cell survival does not (39).…”
Section: Growth Factors and Sphk1 Activationmentioning
confidence: 99%